Handbook on vitamin A tracer dilution methods to assess status and evaluate intervention programs - Haskell, Marjorie J.; Ribaya-Mercado, Judy D.; The Vitamin A Tracer Task Force (International Center for Tropical Agriculture, 2005)
Vitamin A deficiency is a serious public health problem affecting 140 million children and 20 million pregnant women annually in many developing nations worldwide. Vitamin A deficiency can result in anemia, reduced resistance to infection, impaired cellular differentiation, xerophthalmia, and ultimately blindness and death. Because of the detrimental effects of vitamin A deficiency on human health, accurate assessment of vitamin A status is necessary to make informed decisions regarding intervention programs...The purpose of these guidelines is to assist researchers in designing and carrying out studies using the stable isotope dilution technique to assess the efficacy and effectiveness of vitamin A interventions aimed at improving vitamin A status in populations at risk of deficiency.